Bifunctional iminophosphorane-catalyzed enantioselective sulfa-michael addition to unactivated α,β-unsaturated amides - Rozsar, D; Formica, M; Yamazaki, K; Hamlin, TA; Dixon, DJ (American Chemical Society, 2022)
The first metal-free catalytic intermolecular enantioselective Michael addition to unactivated α,β-unsaturated amides is described. Consistently high enantiomeric excesses and yields were obtained over a wide range of alkyl thiol pronucleophiles and electrophiles under mild reaction conditions, enabled by a novel squaramide-based bifunctional iminophosphorane catalyst. Low catalyst loadings (2.0 mol %) were achieved on a decagram scale, demonstrating the scalability of the reaction. Computational analysis revealed the origin of the high enantiofacial selectivity via analysis of relevant transition structures and provided substantial support for specific noncovalent activation of the carbonyl group of the α,β-unsaturated amide by the catalyst.